Epigallocatechin gallate alleviates high-fat diet-induced hepatic lipotoxicity by targeting mitochondrial ROS-mediated ferroptosis - Ding, Shi-Bin; Chu, Xiao-Lei; Jin, Yu-Xuan; Jiang, Jin-Jin; Zhao, Xiao; Yu, Min (Frontiers in Pharmacology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a chronic advanced liver disease that is highly related to metabolic disorders and induced by a high-fat diet (HFD). Recently, epigallocatechin gallate (EGCG) has been regarded as a protective bioactive polyphenol in green tea that has the ability to protect against NAFLD, but the molecular mechanism remains poorly deciphered. Ferroptosis plays a vital role in the progression of NAFLD, but experimental evidence of ferroptosis inhibition by EGCG is limited. Hence, our study aimed to investigate the effect and mechanisms of EGCG on hepatic ferroptosis to mitigate hepatic injury in HFD-fed mice. Methods: Fifty male C57BL/6 mice were fed either a standard chow diet (SCD), a HFD, or a HFD and administered EGCG or ferrostatin-1 (a ferroptosis-specific inhibitor) for 12 weeks. Liver injury, lipid accumulation, hepatic steatosis, oxidative stress, iron overload and ferroptosis marker proteins were examined. In vitro, steatotic L-02 cells were used to explore the underlying mechanism. Results: In our research, we found that EGCG notably alleviated liver injury and lipid accumulation, oxidative stress, hepatic steatosis, decreased iron overload and inhibited ferroptosis in a HFD-induced murine model of NAFLD. In in vitro experiments, using ferrostatin-1 and a mitochondrial reactive oxygen species (MtROS) scavenger (Mito-TEMPO), we found that EGCG remarkably alleviated oxidative stress and inhibited ferroptosis by reducing the level of MtROS in steatotic L-02 cells. Conclusion: Taken together, our results revealed that EGCG may exert protective effects on hepatic lipotoxicity by inhibiting MtROS-mediated hepatic ferroptosis. Findings from our study provide new insight into prevention and treatment strategies for NAFLD pathological processes.